Semantic Primes of Perception from the Perspective of Word Formation - Zaslonkina, Anna (Editura Universităţii „Alexandru Ioan Cuza” Iaşi, 2020)
The object of the present study is the domain of Greimassian semiotic theory. Several previous findings on supraindividual phenomena have been summarized and theoretical underpinnings of the so-called thymic category have been extended. Investigation of such an object discloses the relation between the experiential (which approximates the sensational) and the cognitive nature of perception. Whereas conceptual universals that bear the information on feelings, senses and emotions such as those inherent in the corporal framework which correspond to the basic level of categorization have already been demonstrated, their iconic efficiency in terms of Peircian semiotics is still unclear. Therefore, the aim of the current analysis is to clarify structural-semantic links between derived and root words constituting the thymic lexical corpus of modern English. This paper emphasizes the importance of understanding how the motivational means conditioned by the classification of associative-figurative and evaluative features of the conceptual triad SENSE : FEELING : EMOTION are exteriorised within the thymic category. These characteristics can be developed and enhanced through the iconic reflection of the correlation between the native speakers’ evaluation of the sign acting as a motivator and the expressive as well as gnoseological functions of perception.
Keywords: composite; concept; derivative; icon; word formation